DETERMINATION OF GERMANIUM, GALLIUM, INDIUM AND THALLIUM DISTRIBUTION IN INTERPRODUCTS OF HYDROMETALLURGICAL ZINC PRODUCTION - D. D. Stanojević; M. B. Rajković; D. V. Tošković; M. V. Tomić (Journal of Engineering & Processing Management, 2009)
Nowadays, due to using many rare metals in the most advanced technologies, the demand for these metals is increasing. Rare metals, however, mostly don’t show the property of creating their own mineral deposits, making their production more complicated. Some rare metals, e.g. gallium, germanium, indium and thallium usually accompany zinc ore. In the procedure of hydrometallurgical zinc production, the concentrating of these metals occurs in some interproduct processes, out of which they can be extracted. The possibility of obtaining rare metals from these sources is directly caused by the contents and quantities in specific interproducts. This paper deals with controlling the distribution of rare metals Ga, Ge, In and Tl in hydrometallurgical zinc production, in zinc plant Chemical Industry "Zorka" in Šabac, in order to determine the places and concentration level of controlled rare metals. It is determined that In and Ga are significantly concentrated in specific output mud and precipitates from the process, and that they exist in commercially significant quantities on existing depots of these materials, while it is not the case for Ga and Tl.
Keywords: Distribution; Ghermanium; Ghalium; Indium; Thalium; Zinck